Exploring Investment Awareness: A Student Perspective in South Kalimantan - Rizky Nastiti; Masithah Akbar; Norbaiti Norbaiti; Raden Rara Siti Munawarah (At-Tadbir : jurnal ilmiah manajemen, 2023)
Today's younger generation, especially students, are more aware of technological advances than the older generation. Even so, it is still a question whether they have an awareness of the importance of investment. Therefore, this study aims to analyze the investment awareness of the younger generation, in this case students. This study used a questionnaire as the main data collection instrument by taking a sample of 113 students majoring in economics in South Kalimantan. The results of the study reveal that financial literacy, personal interest and saving behavior have a positive and significant effect on the investment awareness of students. These results indicate that student investment awareness arises from their own awareness where they have the initiative to seek more detailed information about investment and the habit of making financial planning. Furthermore, studying the level of investment awareness can provide important insights for policy makers, and educational institutions on how to increase support for young investors in making sound investment decisions.